Variables that show bullying in a university context (Encuentros, 2016)
In the current study a number of dimensions that determine the coexistence between peers, in a university context, are analyzed. In order to do this, we used the Conduct and Social Experiences in Class Questionnaire, which aims to identify students at risk for aggressive behavior or victimization so as to prevent bullying situations. This instrument was administered to four groups of psychology students, three groups from third semester and one group from fifth semester. The research found that groups with high level of prosocial behavior showed low levels of aggression and victimization. It was also found that most students who were victims were perpetrator too. These findings may interest to psycho-educational practice.Key words: Bullying , aggression, victimization , prosociality , university